Consumption Measurement and Failure Detection in Hot Water Recirculation Systems - Šípal, J. (Elektronika ir Elektrotechnika, 2010)
Measurement of energy to cover heat losses due to hot water recirculation must be precise so that the associated costs can be split among the consumers in a fair way, but it is very challenging due to the low ratio of consumed water to recirculated water. This paper reviews two approved methods of measurement and discusses their advantages and disadvantages. Additionally, it introduces a software enhancement of measurement system that can be used to detect failures in the system, such as leaks. Test of the system and its ability to indicate failures is explored using real data.